Language Politeness of Canteen Traders at Wiralodra University, Indramayu Regency, Reviewed from Leech's Theory - Tarsinih, Eny (Universitas Wiralodra, 2025)
This research aims to describe language politeness of trader in Wiralodra University Indramayu canteen based on Leech maxim 1983. The method used in this research is qualitative research. The type of research used is field research. The data source is the traders in Wiralodra University canteen. The data research is conversation traders with Indonesian language when interact with the partner. This research used fishing technique, speaking technique, and record technique. The steps of data analysis research includes: data reduction, data presentation, and conclusion. Amount of data researched in language politeness is 11 speech. Based on research, there found six maxim of politeness speech. There are three data of tact maxim, three data of generosity maxim, one data of approbation maxim, one data of modesty maxim, two data of agreement maxim, and one data of sympathi maxim. The result of this research indicate that the traders in Wiralodra University canteen used language politeness when communicating.